1997
DOI: 10.1099/00207713-47-1-233
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Minimal Standards for Description of New Taxa in the Order Halobacteriales

Abstract: In accordance with Recommendation 30b of the International Code of Nomenclature of Bacteria, which calls for the development of minimal standards for describing new species, we propose minimal standards for description of new taxa in the order Hulobucteriules. The minimal standards include information on the following characteristics: cell morphology; motility; pigmentation; the requirement for salt to prevent cell lysis; optimum NaCl and MgCl, concentrations for growth and range of salt concentrations enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
472
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(475 citation statements)
references
References 28 publications
1
472
0
1
Order By: Relevance
“…As shown in Table 2, there are two subgroups in the genus Natrialba ; members of one subgroup (Natrialba asiatica JCM 9576 T and JCM 9577) contain a glycolipid (2,6-HSO $ -Manp-α(1 2)-Glcp-α(1 1)-sn-glyceroldiether ; S # -DGD-1) in addition to phospholipids (PG and PGP-Me), and members of the other subgroup (Natrialba magadii NCIMB 2190 T and our two isolates) contain only PG and PGP-Me. This feature would imply that the genus Natrialba constitutes a heterogeneous group and it is not in accordance with the principles of polyphasic taxonomy (Grant & Larsen, 1989 ;Oren et al, 1997). Future studies should clarify the classification of the entire group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2, there are two subgroups in the genus Natrialba ; members of one subgroup (Natrialba asiatica JCM 9576 T and JCM 9577) contain a glycolipid (2,6-HSO $ -Manp-α(1 2)-Glcp-α(1 1)-sn-glyceroldiether ; S # -DGD-1) in addition to phospholipids (PG and PGP-Me), and members of the other subgroup (Natrialba magadii NCIMB 2190 T and our two isolates) contain only PG and PGP-Me. This feature would imply that the genus Natrialba constitutes a heterogeneous group and it is not in accordance with the principles of polyphasic taxonomy (Grant & Larsen, 1989 ;Oren et al, 1997). Future studies should clarify the classification of the entire group.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic tests on strains X21 T and C112 T were carried out in accordance with the recommended standard methods for halobacteria (Oren et al, 1997). Cell motility and shape were examined by phasecontrast microscopy without fixation and by Gram staining with acetic acid fixation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical tests. Unless specified otherwise, tests for phenotypic properties were carried out as indicated in the proposed minimal standards for the description of new taxa in the order Halobacteriales (Oren et al, 1997). Nitrate reduction was tested in liquid SG medium supplemented with 0n5 % NaNO $ .…”
Section: Collection Of Samples and Isolation Of Halophilic Archaeamentioning
confidence: 99%
“…The development of red color in saline environments is a phenomenon which was observed thousand of years ago. Studies in the early 20 th century identified the cause and described several archaeal isolates [6]. Halophilic archaea can accumulate potassium ions intracellularly in order to balance the high salt content of saline environments.…”
Section: Introductionmentioning
confidence: 99%